Rheological studies of Acrylonitrile Butadiene Styrene (ABS) reinforced carbon black blends - Muhammad Shazwan, Harris Shazlan (2019)
Nowadays, effort of combining conductive fillers into ABS making the blends antistatic has utilized plenty of potential applications with high demand on conductive polymer composite, which are not limited to electrical insulating materials any more. Carbon black (CB) is conductive fillers that can be added into ABS. The effects of added CB on the processability of Acrylonitrile–Butadiene–Styrene (ABS) thermoplastic polymers was investigated. The methodology for this experiment is divided by two steps. First, mixing of ABS and CB has been done by changing the weight percent which range from 10% to 50% using internal mixer with 210°C at a screw speed of 5 rpm for 3 minutes and later analysis the trends. Next step, rheological testing that have been done in order to measure the flow properties of composite materials have been evaluated by using Melt Flow Index. The rheological properties was calculated by result of Melt Flow Index. The processing flow decreases as the CB content increases. Next, the rheological properties of ABS reinforced CB blends has shown that flow rate in a polymer is related inversely to viscosity. High CB content in ABS will increases the resistance to flow. Thus reduces the flow rate